Qualities Without the Man (Book Review) - Jayemanne, Darshana (Cosmos and History: The Journal of Natural and Social Philosophy, 2007)
Review of Dominic Pettman, emspan class="sans"Love and Other Technologies: Retrofitting Eros for the Information Age/span/emspan class="sans", New York, /spanFordham University Press, 2006. ISBN: 978-0823226696